Comprehensive analysis of the glutathione S-transferase Mu (GSTM) gene family in ovarian cancer identifies prognostic and expression significance - Zhang, Juan; Li, Yan; Zou, Juan; Lai, Chun-tian; Zeng, Tian; Peng, Juan; Zou, Wen-da; Cao, Bei; Liu, Dan; Zhu, Li-yu; Li, Hui; Li, Yu-kun (Frontiers in Oncology, 2022)
Abstract Background: Ovarian cancer (OC) is one of the most common types of gynecologic tumors worldwide. The glutathione S-transferase Mu (GSTM) is a superfamily of genes that includes five members, termed GSTM1-5. These GSTMs are involved in cell metabolism and detoxification, but their role in OC remains unknown. Methods: Data from multiple public databases associated with OC and GSTMs were collected. Expression, prognosis, function enrichment, immune infiltration, stemness index, and drug sensitivity analyses were utilized to identify the roles of GSTMs in OC progression. RT–qPCR analysis confirmed the effect of AICAR, AT-7519, PHA-793887 and PI-103 on the mRNA levels of GSTM3/4. Results: GSTM1-5 were decreased in OC samples compared to normal ovary samples. GSTM1/5 were positively correlated with OC prognosis, but GSTM3 was negatively correlated with OC prognosis. Functional enrichment analysis indicated that GSTMs were involved in glutathione metabolism, drug metabolism, and drug resistance. Immune infiltration analysis indicated that GSTM2/3/4 promoted immune escape in OC. GSTM5 was significantly correlated with the OC stemness index. GSTM3/4 were remarkedly associated with OC chemoresistance, especially in AICAR, AT-7519, PHA-793887 and PI-103. Conclusion: GSTM3 was negatively correlated with OC prognosis and associated with OC chemoresistance and immune escape. This gene is a potential prognostic biomarker and therapeutic target for OC patients.